Extracorporeal life support in pediatric cardiac dysfunction - Coskun, Kasim O (BioMed Central, 2010)
BACKGROUND: Low cardiac output (LCO) after corrective surgery remains a serious complication in pediatric congenital heart diseases (CHD). In the case of refractory LCO, extra corporeal life support (ECLS) extra corporeal membrane oxygenation (ECMO) or ventricle assist devices (VAD) is the final therapeutic option. In the present study we have reviewed the outcomes of pediatric patients after corrective surgery necessitating ECLS and compared outcomes with pediatric patients necessitating ECLS because of dilatated cardiomyopathy (DCM). METHODS: A retrospective single-centre cohort study was evaluated in pediatric patients, between 1991 and 2008, that required ECLS. A total of 48 patients received ECLS, of which 23 were male and 25 female. The indications for ECLS included CHD in 32 patients and DCM in 16 patients. RESULTS: The mean age was 1.2 ± 3.9 years for CHD patients and 10.4 ± 5.8 years for DCM patients. Twenty-six patients received ECMO and 22 patients received VAD. A total of 15 patients out of 48 survived, 8 were discharged after myocardial recovery and 7 were discharged after successful heart transplantation. The overall mortality in patients with extracorporeal life support was 68%. CONCLUSION: Although the use of ECLS shows a significantly high mortality rate it remains the ultimate chance for children. For better results, ECLS should be initiated in the operating room or shortly thereafter. Bridge to heart transplantation should be considered if there is no improvement in cardiac function to avoid irreversible multiorgan failure (MFO).